Teacherís role: its social importance (Praxis Educativa, 2012)
The beginning of life and the sense of life itself have been a matter of concern for human beings since the origin of humankind, that is why man has always attempted to find an explanation for those questions. Those explanations became, in time, the symbolic framework which served as the basis for the macro narratives that, according to the values held by each society, state the exemplary model that orients human activity. The importance of narration lies in the value the narrator is imbued with, as he who retrieves memories of the past in order to make life possible; life considered as cooperative creation. The narrator, formerly the wizard of the tribes, today, the classroom teacher, assumes the teaching role whose aim is to help others give meaning to life and make sense of it: to understand in order to be able to participate in an active and responsible way in the existing world, and, at the same time, in its design. The function of assisting others to be conscious human beings in this world turns the teacher’s role into a creative act and the enterprise of teaching calls for the integration of strong-willed actors.
Keywords: teaching; creation; meaning; sense; inclusion